Making Canada Home: Snapshots of Syrian and Iraqi Newcomer Cultural Production in the Waterloo Region, 2016-2019 - Vermeyden, Anne Elizabeth; Mohamed, Eid (Refuge, 2020)
Since the beginning of the Syrian Crisis in 2011, millions of refugees from Syria and Iraq have been displaced. Over 25,000 Syrian newcomers settled in Canada between 2015 and 2016.1 The Region of Waterloo, home to a population of approximately 535,000 by 2016,2 was where about 2,000 of these newcomers settled.3 This article argues that these newcomers have used arts and culture to navigate the difficulties of settlement and acculturation. Evidence from newspaper articles, interviews, and participant observation indicates that refugees from Syria and Iraq in this region have utilized dance and theatre to develop community that retains cultural connections and identity linked with Syria and the greater Levantine region. Professional and community arts initiatives spearheaded by refugees showcase how culture and identity are caught up in continuous circulations of culture that are geographically situated in the Canadian context. For Syrian and Iraqi refugees in the Waterloo Region, acculturation, nostalgia, and assimilation are complex and powerful sites of community.